When are analyst recommendation changes influential? - LOH, Roger (Institutional Knowledge at Singapore Management University, 2011)
The existing literature measures the contribution of analyst recommendation changes using average stock-price reactions. With such an approach, recommendation changes can have a significant impact even if no recommendation has a visible stock-price impact. Instead, we call a recommendation change influential only if it affects the stock price of the affected firm visibly. We show that only 12% of recommendation changes are influential. Recommendation changes are more likely to be influential if they are from leader, star, previously influential analysts, issued away from consensus, accompanied by earnings forecasts, and issued on growth, small, high institutional ownership, or high forecast dispersion firms.